FACTORS RELATED TO PATIENT SAFETY CULTURE IN THE INPATIENT PRIMARY HEALTH CARE - Fuji Mahmudah; Hilda Hilda; Arsyawina Arsyawina (Husada Mahakam, 2022)
The culture of patient safety in health services has not been optimally implemented and is an important factor causing patient safety incidents. The purpose of this study was to analyze the relationship between individual factors, leadership, management, and work environment with patient safety culture at the Inpatient Health Center in Samarinda. Analytic observational with cross sectional design. Data were collected using a questionnaire. The research subjects were 79 respondents who were health workers spread over six inpatient health centers in the city of Samarinda. Data were analyzed univariately, bivariately with chi square test and multivariate with multiple logistic regression test. Respondents with a weak patient safety culture were 51.9% and a strong patient safety culture was 48.1%. In individual variables, management and leadership, and work environment, each p-value is 0.001, meaning that there is a significant relationship between individual factors, management, leadership and work environment with patient safety culture. Work environment variable is the most dominant variable related to patient safety culture with p-value = 0.001 (OR = 10.453). There is a significant relationship between individual factors, management, leadership and work environment with patient safety culture. The work environment is the dominant factor that is most closely related to patient safety culture.